Development of a Canva-Based Educational Website as an Innovation in Digital Learning Media - Fitriyani, Nur; Fahri, Ahmad Juliar (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
This research aims to develop an educational website based on Canva as an innovation in digital learning media that supports teachers, particularly Islamic Religious Education (PAI) teachers in both formal and non-formal educational units, in presenting teaching materials more practically, integratively, and easily accessible. The background of this research stems from the challenges of 21st-century education, which demand interactive, efficient learning processes that align with the Sustainable Development Goals agenda (SDG 4: Quality Education). The research method used is Research and Development (R&D) with the Waterfall model, which includes the stages of needs analysis, design, implementation, testing, and maintenance. The developed product contains various learning media, teaching modules, and a list of relevant Artificial Intelligence (AI) applications to support learning. The results of the Black Box Testing method show that all website features function as designed, are responsive, and can be accessed on various devices. This Canva-based educational website is considered suitable for use as a digital learning medium because it can improve teacher efficiency, enrich students' learning experiences, and contribute to the realization of inclusive, innovative, and sustainable education.